Influence of helminth infection on vaginal immunity - Omondi, Fidilia (Department of Clinical Laboratory Sciences, 2023)
Helminth infections induce systemic changes to host immunity and can impact unrelated infections, even those occurring at anatomical sites not normally colonised by the helminths. A few studies have shown that helminths can increase the risk of infection and pathology resulting from sexually transmitted viral infections in the female reproductive tract, however the evidence is limited and the scope of helminth infection on immunity and infection in the female reproductive tract has not been fully elucidated. In this thesis the impact of hookworm infection on immunity in the female reproductive tract and risk of Human Papillomavirus infection in humans was investigated. The influence of helminth infection on B and T cell responses in the female reproductive tract and how this impacts vaccine mediated responses to another viral infection of the female reproductive tract, Herpes Simplex Virus, Type 2 was also assessed in a mouse model. To determine the risk of Human Papillomavirus among hookworm infected participants, we compared the prevalence of Human Papillomavirus infection among hookworm infected and uninfected women. Hookworm infected women were two times more likely to be Human Papillomavirus positive than women with no hookworm infection. Furthermore, hookworm infection was positively associated with the intensity of Human Papillomavirus infection. To determine whether hookworm infection induced changes in vaginal immunity we employed multiplex assays to measure chemokine, cytokine and antibody levels in the vaginal flushes of our study participants. Hookworm infected women displayed an elevated mixed Type 1 (TNF-a, IL-2 and IL-12) and Type 2 (IL-4, IL-5, IL-13, eotaxin and elevated IgG4/ IgE ratio) immune response in the female reproductive tract in xvi comparison to uninfected women. Type 2 immunity was pronounced in hookworm and Human Papillomavirus co-infected women who maintained an elevated Type 2 signature (IL-4, IL-5, IL-13, eotaxin and elevated IgG4/ IgE ratio) and an increased Th2/Th1 ratio in comparison to uninfected women. We then investigated the impact of primary helminth infection on B and T cell immunity in the female reproductive tract using the mouse model of hookworm infection, Nippostrongylus brasiliensis. Nippostrongylus brasiliensis infection of wild type BALB/c mice resulted in increased B cells, IgG1+ B cells and IgG1+ follicular B cells as well as increased effector memory T cells and T follicular helper cells in iliac lymph nodes, which drain the female reproductive tract. We then infected wild type BALB/c mice with Nippostrongylus brasiliensis and immunised them with formalin inactivated Herpes Simplex Virus, Type 2 then challenged them intravaginally with lethal dose Herpes Simplex Virus, Type 2. Nippostrongylus brasiliensis infection did not significantly impact B cell responses to vaccination and subsequent challenge though there was a trend towards lower B cell responses in mice that received Nippostrongylus brasiliensis treatment prior to vaccination. Mice that had prior Nippostrongylus brasiliensis infection, however, had significantly lower effector memory CD4+ T cells than mice that did not have helminth infection before vaccination. In summary, this thesis demonstrates that helminth infection induces Type 2 associated immune changes in the female reproductive tract in humans and alters B and T cell populations in lymph nodes draining the female reproductive tract of mice. Furthermore, in humans, an increased risk of Human Papillomavirus infection and increased intensity of Human Papillomavirus infection was associated with hookworm infection. In mice, a dampening of Herpes Simplex Virus, Type 2 vaccine mediated xvii effector CD4 T cells responses and increased pathology following viral challenge was observed in mice previously infected with Nippostrongylus brasiliensis. The findings in this thesis highlight helminth infection as a significant risk factor for sexually transmitted viral infections and have implications for control of these infections among women living in helminth endemic areas.